Saints and Society in Adam Smith’s Theory of Moral Sentiments: The Influence of Religion and Community on Individual Morality. - Moore, Victoria L. (Tufts University. Tisch Library., 2017)
Smith’s moral theory in The Theory of Moral Sentiments is comprehensive and occasionally ambiguous. Smith at one points says that he is focused on “matters of fact” not “matters of right” (II.i.5.10), while at others moments he concludes that the impartial spectator is “reason, principle, conscience…the great judge and arbiter of our conduct” (III.i.46) and therefore appears to imply that the impartial spectator is able to communicate a transcendent and corrected moral opinion that ought to be obeyed. Within my thesis I explore this tension in Smith’s thought by focusing firstly on the role of religion in his theory in order to determine if the impartial spectator is representative of divine will and can be deemed authoritative because it is divinely ordained. Secondly I analyze the role of society and community in Smith’s theory in order to determine the extent to which the individual can reject and “transcend” the moral standards accepted by their peers in order to ultimately demonstrate that Smith’s theory structurally operates in a way that does not promote, or allow for, the promulgation of universal morals.